Short Communication: Full-length 16S rRNA gene amplicon sequencing reveals baseline indigenous rhizobacterial diversity in Bondowoso Arabica coffee soils, Indonesia - IIS NUR ASYIAH; IMAM MUDAKIR; SUTOYO SUTOYO; MOH DLIYAUDDIN; IRFAN MUSTAFA; ELENA FRANSINA LEONOR LILIPALY (Society for Indonesian Biodiversity, 2026)
Abstract. Asyiah IN, Mudakir I, Sutoyo, Dliyauddin M, Mustafa I, Lilipaly EFL. 2026. Short Communication:Full-length 16S rRNA gene amplicon sequencing reveals baseline indigenous rhizobacterial diversity in Bondowoso Arabica coffee soils, Indonesia. Biodiversitas 27 (7): d270706. https://doi.org/10.13057/biodiv/d270706. The microbiome of the rhizosphere, which remains underexplored in the case of the highland Arabica coffee in Indonesia, might be relevant for the development of environment-friendly farming systems. Here we provide a baseline taxonomic analysis of native rhizobacteria from coffee plantation soils in Bondowoso (Ijen volcanic complex, East Java; 1,282-1,598 m a.s.l.) based on full-length 16S rRNA gene amplicon sequencing (V1-V9, Oxford Nanopore GridION). Rhizosphere soil at five georeferenced subsampling sites was combined to form one composite sample, three technical replicates were prepared and sequenced; these replicates serve to evaluate analytical reproducibility rather than spatial heterogeneity and no biological replication was included. Alpha diversity estimates were uniformly high across replicates (total observed OTUs ≈ 5,576; Shannon H’ ≈ 6.20; Simpson ≈ 0.99), indicating reproducible sequencing of the composite sample. The phylum level was dominated by Pseudomonadota (35%), Actinomycetota (25%), and Myxococcota (15%), and Gaiella occulta, Pseudolabrys taiwanensis, Vicinamibacter silvestris, were the most frequent species. Rare taxa that are known to be functionally relevant under similar frameworks such as Streptomyces rhizosphaerihabitans were also identified. These results represent a first taxonomic catalog of rhizobacteria in this highland coffee system and highlight a set of potential Plant Growth-Promoting Rhizobacteria (PGPR) for further studies. No functional tests were performed; PGPR claims are purely speculative and need to be corroborated by isolation, in vitro, and in planta.